2002
DOI: 10.2165/00007256-200232120-00001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and the Treatment of Clinical Depression in Adults

Abstract: This article critically reviews the evidence that exercise is effective in treating depression in adults. Depression is recognised as a mood state, clinical syndrome and psychiatric condition, and traditional methods for assessing depression (e.g. standard interviews, questionnaires) are described. In order to place exercise therapy into context, more established methods for treating clinical depression are discussed. Observational (e.g. cross-sectional and correlational) and interventional studies of exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
280
0
15

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(302 citation statements)
references
References 179 publications
7
280
0
15
Order By: Relevance
“…The lack of correlation between fitness improvement and reduction in depression symptoms found in this review concurs with other work (Brosse, Sheets, Lett, & Blumenthal, 2002). The recent and growing evidence that improvements in fitness are determined more by genetic factors than levels of exercise (Bouchard et al, 2011;Timmons et al, 2010) could explain this, at least in part, suggesting that it is not improvements from baseline fitness but other aspects of exercise, such as its intensity, perceived intensity, duration or 16 contextual factors, that need to be measured to help explain the mechanism(s) behind physical activity"s positive effect on depression.…”
supporting
confidence: 92%
“…The lack of correlation between fitness improvement and reduction in depression symptoms found in this review concurs with other work (Brosse, Sheets, Lett, & Blumenthal, 2002). The recent and growing evidence that improvements in fitness are determined more by genetic factors than levels of exercise (Bouchard et al, 2011;Timmons et al, 2010) could explain this, at least in part, suggesting that it is not improvements from baseline fitness but other aspects of exercise, such as its intensity, perceived intensity, duration or 16 contextual factors, that need to be measured to help explain the mechanism(s) behind physical activity"s positive effect on depression.…”
supporting
confidence: 92%
“…4 Several limitations have been identified in existing work on the association between PA and psychological outcomes in old age. These include inadequate follow-up periods, reliance on clinical rather than population samples, failure to adjust for important confounders such as physical disability and problems associated with measuring PA. [4][5][6] One important limitation of particular relevance to our study was the failure to examine the factors that mediate the association between PA and mental distress in later life. 5,7 While various biological, social, and cognitive factors were posited as mechanisms linking PA to mental health, researchers have seldom examined mediating factors, or assessed their relative contribution in a single model.…”
mentioning
confidence: 99%
“…In particular, self-esteem has been identified as an important mediating variable in the PA-depression relation. 5,6,12 A positive general self-concept has a known protective effect on psychological distress. Although some researchers have suggested that physical self-esteem, specifically, is central to the association between PA and depression, 13 most evidence supports a link between PA and global self-esteem among older adults.…”
mentioning
confidence: 99%
“…Several hypothetical mechanisms have been suggested, including monoamine activation, hypothalamus-pituitary-adrenal activation or brain-derived neurotrophic factor (BDNF) mediated changes 47) . Among these, BDNF has recently drawn particular research attention.…”
Section: Effect Of Exercise On Moodmentioning
confidence: 99%